Identifikasi Kesesuaian Karakteristik Generasi Y dan Budaya Organisasi terhadap Deviant Workplace Behavior Pada PT. ABC - Sabrina Heriza Rangkuti; - Yuniaristanto; Roni Zakaria (Performa: Media Ilmiah Teknik Industri, 2018)
Generation is a groups consisting of individuals have in common over age range and experience in the same period. Currently there are four generations of working age population in the organization determined based on year of birth, namely boomer generation (1946-1964), X generation (1965-1977), and Y generation (1977-1994). In Indonesia, knowing Y generation is a challenge because the research of this generation is very limited or perhaps even very rarely be contracted with this generation, especially to reviewing the characteristic or perception of this generation. One of the MRO companies in Indonesia has about 4,400 employees and 65% of its employees are Y generation. This MRO company has the vision to be the top 10 MRO companies in the world. Organizational culture is one of the strategies considered by the company. Organizational culture become an important element in desigining norms, attitude and social values that must be considered with an organization to overcome deviant workplace behaviour problems So, the purpose of this study is to characterize the employee Y in the MRO company and to see the relationship of Y generation characteristics and organizational culture to the deviant workplace behavior. The results obtained from this research survey are some characteristics of generation Y according to Murphy (2007) owned by employees Y generation at PT. ABC and only group action characteristics that have an effect on Y generation characteristics on PT. ABC. This can mean the generation of Y employees at PT. ABC has not developed the potential which should belong to Generation Y in general. Like the potential to be optimistic and multitasking that would be very useful to the MRO company but has not had any influence.